The Use of TQM in Educational Training Processes - Ala'a Hakem M. Al-Naser; Raja K .L. Al-Maleki (University of Science and Technology, Yemen, 2014)
ا الكلمات المفتاحية: إدارة الجودة الشاملة، تطبيقات الجودة، التدريب، الإعداد والتدريب التربوي. The Use of TQM in Educational Training Processes Abstract: Training is considered as one of the basic administrative function in the administration for its direct connection in the level of quality management for the workers at any organization, as the preparation and education training a necessary process in the development of the education, especially the educational institute. The research should tackle whatever related to quality and efficiency and how to adapt to them. The problem lies in the clear weakness in the level of quality of the training of the training in the institution including preparation and education training at the Ministry of Training. Also, for the importance of the total quality and employing it in the preparation and education training. Also, the research aimed at investigating the applicability and also to show them and adopt the terminology and the theoretical aspect and the previous study. Then, the two researchers came up with a number of results the most important of which is that the material and moral support. There is a lot of superintendence on educational training. The suggestion and recommendations the most important is the necessity of choosing the administrative leadership based on training for those who are capable of the up-to-date administrative and also inventing new departments of quality control at every training center in preparation and training within Ministry of Education.